The sense of control and power with OVER - Hanić, Jasmina (ExELL, 2013)
The classical category theory uses a homonymy approach, where different meanings of one lexeme are symbolized by the same form without any particular relations between them. Cognitive linguistics reduces this sense arbitrariness and offers mechanisms of meaning extensions, one of which is the theory of conceptual metaphor. In this paper, we study some aspects of the particle OVER as a formative element in verbs in relation to Langacker’s (1987) distinction between trajector and landmark. The analysis here focuses on some metaphors for power and control within the framework of cognitive linguistics. Verbs formed with OVER will be shown to behave differently depending on the metaphors which underlie them.